2021
DOI: 10.1002/pi.6235
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility, crystallization and mechanical properties of poly[(3‐hydroxybutyrate)‐co‐(4‐hydroxyvalerate)]/poly(propylene carbonate)/poly(vinyl acetate) ternary blends

Abstract: A ternary blend of poly [(3-hydroxybutyrate)-co-(4-hydroxyvalerate)] (P34HB), poly(propylene carbonate) (PPC) and poly(vinyl acetate) (PVAc) was initially melt-blended in an effort to obtain an excellent balance of mechanical performance. The effect of PVAc content on the miscibility, phase morphology, thermal behavior, isothermal melt crystallization and mechanical properties of P34HB/PPC/PVAc ternary blends was systematically investigated. Dynamic mechanical analysis indicated that P34HB and PPC were immisci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Melt blending has been used to create the ternary blends of P34HB, poly(propylene carbonate) (PPC) and PVAc. 24 The findings demonstrated that there was poor compatibility between P34HB and PPC and poor compatibility between PVAc and PPC. PVAc was mixed in P34HB and refined the dispersed PPC phase by reducing the interfacial tension.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Melt blending has been used to create the ternary blends of P34HB, poly(propylene carbonate) (PPC) and PVAc. 24 The findings demonstrated that there was poor compatibility between P34HB and PPC and poor compatibility between PVAc and PPC. PVAc was mixed in P34HB and refined the dispersed PPC phase by reducing the interfacial tension.…”
Section: Introductionmentioning
confidence: 95%
“…Amorphous P34HB increased and P34HB and PLA became more compatible, so that the ternary blends exhibited good toughness and stiffness balance. Melt blending has been used to create the ternary blends of P34HB, poly(propylene carbonate) (PPC) and PVAc 24 . The findings demonstrated that there was poor compatibility between P34HB and PPC and poor compatibility between PVAc and PPC.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the chain length is an ultimate contributor to the properties of PHA polymers . Although P­(3HB) has comparable tensile strength and a melting point (175 °C) to polypropylene (PP), the manufacturing window is too limited for practical application. , Copolymerization of scl-PHA, such as P­(3HB), improves its mechanical characteristics to compensate for these shortcomings. P­(3HB- co -3HV), for example, was created by adding 3-hydroxyvalerate (HV) into P­(3HB) to create a copolymer that is robust, flexible, and durable with increased thermal processing capabilities.…”
Section: Poly(hydroxyalkanoates (Pha) Origin Types Properties and Bio...mentioning
confidence: 99%
“…To overcome these, the incorporation of other compatible polymers, essential oils, and nanoparticles in the PHB matrix emerges as an economically viable approach, yielding innovative materials with targeted properties. [ 10 ] The inclusion of supplementary biopolymers like poly(ε‐caprolactone), [ 11 ] poly(vinyl acetate), [ 12 ] poly(lactic acid) (PLA), [ 13 ] and poly(ethylene glycol) (PEG) [ 14 ] into the PHB matrix shows great promise toward effectively enhancing the overall potential of PHB to its fullest capacity. One of the most used polyesters, poly(lactic acid) is used in the production of biodegradable films, owing to its nontoxic nature, excellent transparency, and mechanical robustness in the resulting films.…”
Section: Introductionmentioning
confidence: 99%